Clouston Syndrome: Report of a Jordanian Family with GJB6 Gene Mutation - Rand Murshidi; Heba Al-lala (Case Reports in Dermatological Medicine)
Ectodermal dysplasias (ED) encompass a collection of conditions wherein the development of two or more structures derived from the ectoderm exhibits abnormal patterns. One example of such a rarity within the spectrum of ectodermal dysplasias is hidrotic ectodermal dysplasia, also known as Clouston syndrome. This particular variant is distinguished by a triad of clinical characteristics, which encompass partial-to-complete alopecia, nail dystrophy, and palmoplantar hyperkeratosis. It stands as a scarcely encountered autosomal-dominant inherited disorder, resulting from a mutation in the GJB6 gene that encodes the gap junction protein connexin 30. We hereby document the case of a forty-five-year-old Jordanian woman who presented with alopecia affecting the scalp, eyebrows, and eyelashes, in addition to nail dystrophy. Interestingly, she did not manifest palmoplantar keratoderma. It is worth mentioning that several members of her extended family also manifested similar clinical features. Subsequent genetic testing conclusively established the diagnosis of Clouston syndrome. In light of this diagnosis, comprehensive counseling was extended to the patient.